Characterization of Ovarian Lipid Composition in the Largemouth Bronze Gudgeon (Coreius guichenoti) at Different Development Stages - Jian Zhu; Nanjun Hu; Yao Xiao; Xiaohong Lai; Lingjiao Wang; Yufeng Song (Fishes, 2024)
The largemouth bronze gudgeon has experienced a sharp drop in its natural population and has been listed as a protected species in China. The frequent occurrence of ovarian development obstruction from stage III to IV has restricted artificial propagation. Due to lipids being a crucial factor for ovarian development, this study aimed to characterize the ovarian lipid profile at different development stages in largemouth bronze gudgeons. Using UPLC-MS/MS, 1353 lipids belonging to 46 subclasses were identified in ovaries from largemouth bronze gudgeons. The results showed that glycerolipids and glycerophospholipids were the dominant lipids during ovarian development. Lysophosphatidyl choline (LPC), phosphatidyl choline (PC), and phosphatidylserine (PS), as the crucial phospholipids for ovarian development, were significantly reduced from stage III to IV. This may be the main cause of ovarian development obstruction for largemouth bronze gudgeons. Meanwhile, the enrichment analysis revealed that lipid metabolites are present at different ovarian development stages. Glycerophospholipid, linoleic acid, and linolenic acid metabolism were significantly enriched at stage IV. This study shows the complete picture of the ovarian lipid composition profile, and also discovers that phospholipids may be the limiting factor for ovarian development; these findings offer a theoretical basis for the artificial propagation and release of the largemouth bronze gudgeon.